Application of thermal performance evaluation methods for assessing wood wall panels - Giglio, Thalita Gorban Ferreira (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
The aim of this research work is to analyse the applicability of building thermal performance evaluation methods for assessing wood wall panels. The method consists of comparative analysis, in which wood wall panels were alternated in a house prototype. Through a simulation tool, indoor temperature data were obtained, which were analyzed through the application of the building performance standard proposal, and also through application of the discomfort hours method. In addition, an evaluation was carried out based on existing simplified methods. Finally, an analysis on the compatibility of the results from different methods was carried out. Some differences were found in the results obtained from different methods, which contributes for the discussion of aspects that should be revised in those standards, in order to improve the thermal performance evaluation of alternative construction systems.